2010
DOI: 10.1055/s-0030-1255858
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lymph node metastasis associated with deeper invasion by early adenocarcinoma of the esophagus and cardia: study based on endoscopic resection specimens

Abstract: This study suggests that lymph node metastasis risk for m3 and submucosal AEC may be lower than has been assumed on the basis of surgical series, and that current guidelines are valid regarding suitability of m3 AECs for endoscopic therapy. It may also suggest that selected patients with submucosal cancers are also eligible for endoscopic management. Confirmation of these results is needed in larger series with longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 14 publications
(17 reference statements)
4
64
2
3
Order By: Relevance
“…A recent systematic review reported no evidence of nodal metastasis in patients with a final stage of HGD 72. Further stratification of these superficial lesions as in table 8 yields additional prognostic information in that the risk of nodal metastasis correlates with the depth of penetration into the layers,229 234 but not all the studies have confirmed this 230 236…”
Section: Management Of Dysplasia and Early Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…A recent systematic review reported no evidence of nodal metastasis in patients with a final stage of HGD 72. Further stratification of these superficial lesions as in table 8 yields additional prognostic information in that the risk of nodal metastasis correlates with the depth of penetration into the layers,229 234 but not all the studies have confirmed this 230 236…”
Section: Management Of Dysplasia and Early Cancermentioning
confidence: 99%
“…It is still unclear whether T1sm1 cancer (invading the superficial submucosa within 500 µm) can be confidently treated by ER, and although series from Amsterdam and Wiesbaden suggest this carries a low risk of lymph node metastases,230 234 237 not all the literature supports this 72 236. This debate is further complicated by the technical challenges faced by the pathologist to accurately identify the submucosal invasion depth on the ER specimen.…”
Section: Management Of Dysplasia and Early Cancermentioning
confidence: 99%
See 3 more Smart Citations